The Adaptation of the Social Curiosity Scale into Turkish: A Validity and Reliability Study - Elban, Mehmet; Aslan, Selçuk (My University, 2022)
Recently, interest in curiosity-related studies in the national education literature has increased. However, there is a research gap in the studies related to the social curiosity of individuals and measuring the social type of curiosity. The current research aimed to adapt the Social Curiosity Scale (SCS) developed by Renner (2006) into Turkish to contribute to the national literature. Undergraduate and graduate students studying at Turkish state universities constitute the research sample. The scale’s Turkish version’s exploratory (n=279) and confirmatory (n=310) factor analyzes were performed. In the exploratory factor analysis, the total variance explained by the two-factor and 9-items Turkish form is 63.70%. The first and second-level confirmatory factor analyses confirmed the two-factor model (General Social Curiosity and Covert Social Curiosity) obtained before as a result of exploratory factor analysis. Thus, the results of exploratory and confirmatory factor analysis revealed that the construct validity of the scale was ensured. The Cronbach Alpha internal consistency coefficient ranged between .83 and .85 for the whole scale and its subscales. These results indicated that the scale was highly reliable. It is thought that the scale will contribute to research in many fields such as psychological counseling, media research, and education.
Keywords: Curiosity; General Social Curiosity; Covert Social Curiosity